Phylogenetic and adaptive components of the anuran advertisement call correlate with temporal species co-occurrence. (4th September 2018) - Garey, Michel Varajão; Provete, Diogo B; Gonçalves-Souza, Thiago; Ouchi-Melo, Lilian Sayuri; Haddad, Célio F B; Rossa-Feres, Denise C
Abstract: Vocalization is one of the major means of communication in animal groups and is crucial in anuran mate recognition. Animal calls consist of spectral and temporal parameters, whose evolution can be influenced by environmental and evolutionary constraints. At the same time, acoustic niche partitioning plays a key role in determining species co-occurrence. However, little is known about how the interplay between the mode of evolution of call parameters and environmental factors affects species co-occurrence. Here, we analysed seven spectral and temporal call parameters of 19 pond-dwelling anuran species from south-eastern Brazil. We recorded the spatial and temporal occurrence of species over 18 months in 13 water bodies. Whereas the environment had a stronger effect than phylogenetic relationships on temporal occurrence, niche conservatism was the main predictor of spectral parameters. The advertisement call was related to neither spatial nor temporal species co-occurrence. However, species with the highest temporal co-occurrence showed greater differences in temporal call parameters. Our study demonstrates how the phylogenetic and adaptive components of the call affect anuran species co-occurrence at the metacommunity scale.